Efektifitas Kepemimpinan Lembaga Pendidikan Islam Dalam Peningkatan Mutu Lulusan - Anggun Feronika; Jamrizal Jamrizal; Kasful Anwar Us (Journal of Creative Student Research, 2023)
Leadership is a skill that a person has and differentiates him from other leaders. This is the essence of the different types of leadership, so that the types and styles of leadership also have differences, not only in the type of leadership based on the position and position held, but also in the types of leadership that exist. Meanwhile, an Islamic education leader is a figure who is not only a leader of an Islamic institution such as a school, but a leader who can be a role model for others based on his morals which carry positive moral values ​​by applying Islamic principles. The quality of an educational institution can be determined by several supporting components such as curriculum, funding and supporting infrastructure for the educational institution. The quality of graduates is the quality of the school where the students at the school are qualified because of the input and output at the school. The quality of graduates is also greatly influenced by school stakeholders who can support the smooth running of the school. Therefore, the principal's strategy in educational institutions/schools has a significant impact on improving the quality of graduates in the school so that it can produce the best and most competitive graduates.